Leadership and firm entrepreneurial performance in county governments in Kenya - Nandwa J. Musambayi (Journal of Global Entrepreneurship Research, 2018)
The purpose of the study was to evaluate the influence of county government innovative leadership on the entrepreneurial firm performance in Kenya. The Multiple regression model was used to assess the innovative leadership and identify the influencing factors particularly on entrepreneurial firm performance. Data was collected through structured questionnaires, with a total sample of 80 respondents, selected from 20 of the 47 county units in Kenya. Data was analysed using Excel statistical tool. Results show that although county governments have programs to support entrepreneurs within their areas of jurisdiction the programs do not have a statistically significant influence on the entrepreneurial firm performance. Direct support such as credit provision in addition to promoting entrepreneurship training were not adequate. It is thought if these areas are addressed, county government leadership can positively influence firm performance and entrepreneurship development in the country. The county governments, through initiatives such as business incubators, favourable policy formulation and regulation could play an important role in changing the performance of entrepreneurial firms. They could also support them in formulating effective entrepreneurship strategies.
Keywords: 650; Innovative leadership; Devolved units; Entrepreneurial firm performance; Influences; County governments; SMEs